Sound tracks : popular music, identity and place / John Connell and Chris Gibson. - Connell, John, 1946- (Critical geographies ;, 2002)
'Sound Tracks' traces the relationships between music, space and identity, from inner city scenes to the music of nations, to give a wide-ranging perspective on popular music which also examines the influences of culture, economics and technology.